Does Attitude Translate into Intention? Assessing the Empirical Evidence of Attitude-Intention Relationship in the Purchase of Energy Efficient Vehicle (EEV) among Malaysian Consumers - Noor, Nor Azila Mohd; Sari, Mohd Norsam Mohd; Muhammad, Azli; Isa, Filzah Md (CENTRAL ASIA AND THE CAUCASUS, 2024)
Despite warnings about limited fossil fuel as well as the detrimental impacts of burning such fuels, the number of conventionally fueled vehicles in use is growing worldwide. While energy efficient vehicles (EEVs) produce far less emissions and provide power from renewable sources, EEVs are yet to get full acceptance from the local market and the penetration rate is still low. In Malaysia, the sales trend shows that there is a low level of EEV purchased, where energy efficient vehicle only owned 3 percent of market share in Malaysian automotive industry. To fill this gap, this study focuses to examine the relationship between consumers’ attitude towards EEV and their intention to purchase energy efficient vehicle. Data was collected using quantitative approach through mall intercept survey method at ten selected malls in Peninsular Malaysia. Respondents were intercepted at the entrance of the mall and were invited to take part in the survey. The complete process of data collection took five months and comprised a total of 515 respondents. The hypothesis in the present study was tested using Partial Least Squares (PLS). The analysis revealed a positive relationship existsbetween consumers’ attitudes on EEVs and intention to purchase EEVs. The present study provides recommendations, limitations, and suggestions for future study.